Update on the Evaluation and Management of Brief Resolved Unexplained Events (Previously Apparent Life-Threatening Events) - Zwemer, Eric; Claudius, Ilene; Tieder, Joel (Reviews on Recent Clinical Trials, 2017)
Background: The thirty-year-old term “apparent life-threatening event” (ALTE) is difficult to apply in clinical practice and research. The American Academy of Pediatrics now defines these events as brief resolved unexplained events (BRUEs), stratifies infants based on the risk of recurrence or of a serious underlying condition, and offers evidence-based management recommendations for infants at lower-risk. Objective: To review recent ALTE literature as it relates to BRUEs. Method: Articles were identified by searching several clinical databases. English-language articles from January 2006 to August 2016 that address ALTEs or BRUEs were included. Results: Significant variation exists in the evaluation and management of patients diagnosed with BRUE. Research demonstrates low utility of most diagnostic testing, including prolonged cardiorespiratory monitoring, in the well-appearing infant without an obvious etiology. Risk factors for recurrent adverse events or significant underlying pathology include young age, prematurity, and presence of multiple events. There is little evidence to provide guidance for the management of higher-risk infants. Conclusion: BRUE is a diagnosis of exclusion to be applied when there is no apparent etiology after performing an appropriate history and physical examination. Lower-risk infants should not undergo routine diagnostic testing and should not be admitted solely for cardiorespiratory monitoring. Higherrisk infants are more likely to benefit from diagnostic testing and admission; however, routine screening testing is unnecessary, and the history and physical should guide the clinician's approach. Prospective research is needed to understand the incidence of BRUEs, outcomes in lower and higher-risk infants, and the utility of diagnostic testing in higher-risk infants.
Keywords: risk stratification